Mechanical, Durability And Rheology Properties Of Ultra High Performance Concrete (UHPC) With Low Cement Content. Issue 1 (November 2021) - Zahid, M Z A M; Bakar, B H A; Nazri, F M; Alasmari, H; Latiff, M F P M; Ayob, A; Muhammad, K; Ahmad, M M; Manaf, B H A; Ishak, M K
Abstract: This current study attempts to investigate the mechanical, durability as well as rheology properties of Ultra-High Performance Concrete (UHPC) with low cement content and using coarse aggregate. The cement content used in UHPC mix in current study was 800 kg/m3. The slump flow, compressive strength, splitting tensile strength, modulus of elasticity, water absorption and water penetration tests were conducted to determine the workability, mechanical and durability properties of explored UHPC mixture. The test results show that the above properties were exceptional and comparable with other UHPC mixtures.